Relative advantage as mediating variables on factors influencing adoption of internet TV - Abdul Latiff, Dzaa Imma (2019)
Internet TV in Malaysia which uses open Internet Protocol is becoming every consumer's favourite for its portable feature that allows media to be accessed through broadcasts TV without having to be at a specific place. Tonton or tonton.com.my and Astro Go are among the award-winning TV and video portals which offer online catch-up and live television services, and premium paid content. Claiming its popularity in 2013, more Internet TV service providers such as Iflix, Viu and Netflix are made available for Malaysian users recently. The arrival of Internet TV has shaken the traditional revenue from advertisements as television is no longer the main medium of businesses' product promotion. Many studies have mainly taken an economic and technological approach but less on consumers’ needs such as Internet TV, is rarely studied in Malaysia. Limited scholarly research and knowledge about this innovative technology have been conducted. Thus, the importance of this study is to identify the factors that predict consumers’ decisions to adopt Internet TV. In identifying the innovation factors that contribute to Internet TV adoption, a theory of Diffusion of Innovation by Rogers (2003) has been used in this study. The adoption factors are the relative advantage, ease of use, compatibility, trialability and observability. Rogers also mentioned that the importance of unique attributes of Internet TV and personal characteristics were also used in this study. This sequential explanatory mixed methods study investigates the factors that influence users’ adoption of Internet TV. In the first phase, the quantitative survey was designed using a self-administrated questionnaire. All variables were measured through scales previously used by other researchers. The scales were checked for convergent and discriminant validity using Confirmatory Factor Analysis (CFA) and data analysis using Structural Equation Modelling (SEM) under AMOS software on 518 respondents in Malaysia. Meanwhile, the qualitative phase has identified 12 informants from the quantitative data analysis. A thematic analysis was used to interpret the data from a semi- structured interview. Results of the quantitative and qualitative reported that innovation diffusion attributes, specific attributes of Internet TV and personal characteristic overall influence people to adopt Internet TV. Meanwhile, specific attributes of Internet TV reported being better than traditional TV. Moreover, the two attributes from content (variety) and technology (interactivity) were identified as specific attributes of Internet TV that affect the overall use. The SEM analysis determined the hypotheses' study and overall influence the adoption. However, demographic characteristics were found insignificant except for education. The relative advantage as a mediating construct, however, showed an insignificant effect. The qualitative results are overall in line with quantitative findings and contribute a better understanding of factors that influence users to adopt Internet TV. This study contributes to provide various recommendations to the policymaker, media practitioners (broadcasters and content providers), an expanded theory where relative advantage was used as a mediating effect and the use of mixed method strategies. It is hoped that the suggestions may be beneficial to further understand user’s behavior among the competitive Internet TV providers and how this may affect advertising and traditional business models.